2004
DOI: 10.1021/jo0486995
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a New Class of Furan-Fused Tetracyclic Compounds Using o-Quinodimethane Chemistry and Investigation of Their Antiviral Activity

Abstract: The synthesis and evaluation of antiviral activity of new furan-fused tetracyclic compounds are described. The syntheses were satisfactorily achieved on the basis of o-quinodimethane chemistry, using furan-containing benzocyclobutene derivatives as a substrate, in high generality and stereoselectivity. The various derivatives thus synthesized were examined on their inhibitory activity on virus growth using a hemagglutinin (HA) method, leading to a discovery of promising candidates for new antiviral drugs havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 9 publications
(8 reference statements)
0
23
0
2
Order By: Relevance
“…Ausgehend von einer tetracyclischen furanhaltigen Leitstruktur [44] synthetisierten Nemoto und Mitarbeiter eine Bibliothek aus mehrfach anellierten Furanderivaten mit naturstoffähnlicher Architektur. [45] Das Strukturgerüst wurde über eine intramolekulare [4+2]-Cycloaddition von o-Chinodimethanen synthetisiert, wobei letztere durch thermische Ringöffnung von Benzocyclobutanderivaten zugänglich sind (Schema 12). [46] Mit [42,43,47] manche hemmen außerdem auch die Cdc25B-Phosphatase.…”
Section: Mehrfach Anellierte Furanderivateunclassified
“…Ausgehend von einer tetracyclischen furanhaltigen Leitstruktur [44] synthetisierten Nemoto und Mitarbeiter eine Bibliothek aus mehrfach anellierten Furanderivaten mit naturstoffähnlicher Architektur. [45] Das Strukturgerüst wurde über eine intramolekulare [4+2]-Cycloaddition von o-Chinodimethanen synthetisiert, wobei letztere durch thermische Ringöffnung von Benzocyclobutanderivaten zugänglich sind (Schema 12). [46] Mit [42,43,47] manche hemmen außerdem auch die Cdc25B-Phosphatase.…”
Section: Mehrfach Anellierte Furanderivateunclassified
“…This new finding inspired us to examine the structure-activity relationships of its congeners, aiming at the discovery of new candidates for antiviral drugs. 91) As a preliminary study, the antiviral activity was surveyed using the assay method of hemagglutinin (HA) titers. 92) HVJ in LLC-MK2 cells was used for the assay, and the inhibitory activity on the virus growth was assessed as minimum inhibitory concentrations (MIC), which are summarized in Fig.…”
Section: Synthesis and Medicinal Chemistrymentioning
confidence: 99%
“…96) For example, bafilomycin A1 has been reported to exert inhibitory effects on influenza virus growth through specific inhibition of vacuolar-type proton pump to raise the pH in endosomes and lysosomes. 91) To examine whether drug 10 could exert a similar effect, acidification of intracellular compartments under influence of the drug was monitored by vital fluorescence microscopy with acridine orange. 97) This examination revealed that the amount and intensity of fluorescence in the drugtreated cells were almost identical with the control cells, implying that the drug did not affect the acidic environment of intracellular compartments, which causes the uncoating process.…”
Section: Synthesis and Medicinal Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…[1] In the course of our model studies on the synthesis of furan-fused polyketides, halenaquinone, and xestoquinone, [2] we found that dihydrofuran-fused tetracyclic compounds, represented by general structure 1, exert notable antiproliferative effects against viruses, including influenza A and B. [3] More recently, we also reported that this class of compounds can enhance hyperthermiainduced apoptosis in human lymphoma U937 cells. [4] Novel structural characteristics make them a promising lead compound for the discovery of a new type of therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%